DINAMIKA MINAT MENJADI GURU: PENGARUH PERSEPSI PROFESI DAN DUKUNGAN KELUARGA MELALUI MOTIVASI - Putri, Arvianti Farah Natsya; Tanzilah, Syahda Adnindiya; Utama, Dian Herdiana (Comm-Edu (Community Education Journal), 2024)
This study investigates the factors influencing the interest of Physical Education students in becoming teachers. Among 53 respondents, it was found that a positive perception of the teaching profession contributes to increased motivation, subsequently enhancing the interest in pursuing a teaching career. However, the family environment does not directly influence motivation. The implication is that educational institutions can enhance students' understanding and motivation towards the teaching profession and collaborate with families to support students' motivation. Future research could expand the sample and consider contextual factors, as well as conduct cross-cultural studies to gain broader insights into this phenomenon.